STRATEGI PARTAI KEBANGKITAN BANGSA (PKB) DALAM PEMENANGAN PASANGAN JOKO WIDODO-MUHAMMAD JUSUF KALLA PADA PEMILIHAN PRESIDEN DI KABUPATEN INDRAGIRI HILIR TAHUN 2014 - Lasmaria "; M.Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Presidential Election is a performance conduced by country that recognizes itself as a democratic state. This research aim to obtaining picture about strategy Partai Kebangkitan Bangsa (PKB) the winning pair Joko Widodo and Muhammad Jusuf Kalla on the Presidential Election in the Indragiri Hilir district 2014. Strategy is some of tactic to achieve the objectives that have been prepared and that which has been applied. Theory used in this research is democracy, political party, strategy and patron-client. Data collecting technique that writer use is interviews and documents. Whereas the data analysis was done descriptively. The result showed that strategy Partai Kebangkitan Bangsa (PKB) the winning couple Joko Widodo and Muhammad Jusuf Kalla in the Presidential Election in the Indragiri Hilir district 2014 by : (1) Ofensif Strategy, consist of (a) Developing a network outside political parties, (b) Support of Indragiri Hilir community, (c) Improving the member amount. (2) Defensif Strategy, consist of (a) Maintaining sound granaries, (b) Political recruitment, (c) Political socialization. The potential and strength that is used as a support the winning pair Joko Widodo and Muhammad Jusuf Kalla is : (1) Partai Kebangkitan Bangsa the winning legislative elections 2014, (2) Partai Kebangkitan Bangsa increase the number of seats DPRD (Indonesian legislatives) in legislative elections, (3) The structure of the winning team mate Joko Widodo and Muhamamd Jusuf Kalla.Key words : Strategy, Partai Kebangkitan Bangsa, Presidential Elections